Briefly, a delicious life eaudiobook - Stevens, Nell (Simon & Schuster Audio, 2022)
*A Cosmopolitan Best Book of Summer * One of BuzzFeed 's Most Anticipated LGBTQ+ Books* An "exquisite...too lovely to bear" ( The New York Times Book Review ) debut novel from an award-winning writer: a playful and daring tale about a teenage ghost who falls in love with the writer George Sand. In 1473, fourteen-year-old Blanca dies in a hilltop monastery in Mallorca. Nearly four hundred years later, when George Sand, her two children, and her lover Frederic Chopin arrive in the village, Blanca is still there: a spirited, funny, righteous ghost, she's been hanging around the monastery since her accidental death, spying on the monks and the townspeople and keeping track of her descendants. Blanca is enchanted the moment she sees George, and the magical novel unfolds as a story of deeply felt, unrequited longing—a teenage ghost pining for a woman who can't see her and doesn't know she exists. As George and Chopin, who wear their unconventionality, in George's case, literally on their sleeves, find themselves in deepening trouble with the provincial, 19th-century villagers, Blanca watches helplessly and reflects on the circumstances of her own death (which involved an ill-advised love affair with a monk-in-training). Charming, original, and emotionally moving, this "deeply wild debut follows the unconventional love triangle" ( Cosmopolitan ) between George, Chopin, and Blanca—a gorgeous and surprising exploration of artistry, desire, and life after death.